2020
DOI: 10.1016/j.aci.2020.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Predictive modeling of turning operations under different cooling/lubricating conditions for sustainable manufacturing with machine learning techniques

Abstract: Sustainable manufacturing is one of the most important and most challenging issues in present industrial scenario. With the intention of diminish negative effects associated with cutting fluids, the machining industries are continuously developing technologies and systems for cooling/lubricating of the cutting zone while maintaining machining efficiency. In the present study, three regression based machine learning techniques, namely, polynomial regression (PR), support vector regression (SVR) and Gaussian pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Quality control capability (QCC) is considered an essential component of a manufacturing unit (Cica et al, 2020 ; Eslamirad et al, 2020 ; Rana et al, 2020 ). Silbernagel et al ( 2020 ) said that QCC is a process by which manufacturing firms can assess and review factors involved in a manufacturing firm’s production quality.…”
Section: Theoretical Background and Development Of Conceptual Modelmentioning
confidence: 99%
“…Quality control capability (QCC) is considered an essential component of a manufacturing unit (Cica et al, 2020 ; Eslamirad et al, 2020 ; Rana et al, 2020 ). Silbernagel et al ( 2020 ) said that QCC is a process by which manufacturing firms can assess and review factors involved in a manufacturing firm’s production quality.…”
Section: Theoretical Background and Development Of Conceptual Modelmentioning
confidence: 99%
“…Currently, the most widely used cooling/lubricating techniques with a low negative effect on the environment and human operator's health are dry cutting, cryogenic cooling, and minimum quantity lubrication (MQL), etc. [90].…”
Section: Cryogenic Coolingmentioning
confidence: 99%
“…To eliminate these problems, dry machining is used in which the need for cutting oils is eliminated. Dixit et al [90] reported that the use of dry machining significantly minimized air and water pollution. They called dry cutting an eco-friendly process.…”
Section: Dry Cuttingmentioning
confidence: 99%
“…Neural Network applications have been applied for tool tip dynamics, stability and optimization problems [36,44,87,88]. Misaka et al [89] considered Neural Networks, under the form of CNN, based on camera images of the metal cutting processing for machining parameters extraction, obtaining a model accuracy of 85.5% and a precision of 92.9%.…”
Section: Modelingmentioning
confidence: 99%
“…Modeling [43,44]: there are several applications that require to model and predict a phenomenon related to the machine technology, for example, it is useful to determine the correct material removal or the most suitable cooling/lubricating technology to improve the equipment sustainability.…”
mentioning
confidence: 99%